2007
DOI: 10.2466/pms.105.2.458-468
|View full text |Cite
|
Sign up to set email alerts
|

Imagery Intervention in Open and Closed Tennis Motor Skill Performance

Abstract: To assess use of imagery intervention in performance of two tennis motor skills the quasi-experimental design included a pre- and posttest and a control group. The tennis service shot and service receiving skill were selected as representative of open and closed skills, respectively. 48 subjects, male tennis players, whose ages ranged from 16 to 18 yr. (M = 17.2), were divided into two groups: (1) Technical practice only which was used as control group and (2) Imagery group who received both imagery and techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 28 publications
2
28
0
Order By: Relevance
“…Although the amount of uncertainty conveyed by the experimental situation is somewhat limited (this is not a real rally in situ), the present study highlights the benefits of a MI training program on a stroke which directly depends on the opponent’s behaviour. This finding extends previous results focusing primarily on the effects of MI on the tennis serve [ 20 , 22 , 24 – 25 ]. In a recent study, Gaggioli et al [ 40 ] demonstrated the positive effect of MI on coordination in a complex motor skill involving synchronization of upper and lower limb movements.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Although the amount of uncertainty conveyed by the experimental situation is somewhat limited (this is not a real rally in situ), the present study highlights the benefits of a MI training program on a stroke which directly depends on the opponent’s behaviour. This finding extends previous results focusing primarily on the effects of MI on the tennis serve [ 20 , 22 , 24 – 25 ]. In a recent study, Gaggioli et al [ 40 ] demonstrated the positive effect of MI on coordination in a complex motor skill involving synchronization of upper and lower limb movements.…”
Section: Discussionsupporting
confidence: 89%
“…Previous research provided evidence of beneficial effects of MI practice in both young and adult tennis players [ 20 – 25 ]. As MI is known to be more effective in closed skills, where the environment is predictable [ 22 ], most of these experiments focused on the tennis serve, which substantially contributes to win or gain advantage in the point. Data showed that, to be effective, MI has to be congruent with physical practice.…”
Section: Introductionmentioning
confidence: 99%
“…These developmental trends supported the view that MI training is feasible for pediatric rehabilitation in typically developing children as young as 5 years of age. The few experimental studies of AO/MI training in typically developing children (e.g., Atienza et al, 1998; Coelho et al, 2007; Guillot et al, 2015) and children with developmental motor disorders have shown great promise (Wilson et al, 2002, 2016a; Buccino et al, 2012; Sgandurra et al, 2013). For example, Guillot et al (2015) found that embedding MI during a high intensity intermittent tennis training for typically developing children enabled the development of physical fitness and the preservation of stroke performance.…”
Section: Introductionmentioning
confidence: 99%
“…Although previous studies have indicated that athletes can benefit from using imagery in sport to enhance performance [3, 9] , in the highly demanding field of open sports with unpredictable circumstances as seen in soccer, the challenges players face can be diverse [10, 11] . Cross-sectional studies recently have revealed that soccer players are involved with different types of cognitive and motivational imagery due to their cognitive abilities and specific situational demands as well.…”
Section: Introductionmentioning
confidence: 99%